Morcillo, Marta García. Las ventas por subasta en el mundo romano: la esfera privada. Barcelona, Universidad de Barcelona, 2005, 372 pp. isbn 8447530175. - Funari, Pedro Paulo A. (Revista Archai, 2010)
.